Patient satisfaction in the outpatients' chemotherapy unit of Marmara University, Istanbul, Turkey: a staff survey - (:unkn) unknown (BMC, 2002)
Background: We conducted a survey to find out how patients feel about the care they receive in the outpatient chemotherapy unit of Marmara University Hospital. Methods: The American College of Physicians Patient Satisfaction survey translated into Turkish was used. A meeting was held with all involved staff, before conducting the survey, to review the purpose and determine the process. The study was conducted with 100 random patients. Results: Consistent with cancer frequency, most patients had either lung, colorectal or breast cancer. Their insurance was government sponsored in close to 90%. The educational levels were above Turkish median but consistent with the area the hospital is serving. They were coming to the unit on average 8.5 months. The responses were not influenced by the surveyed diagnosis, age, sex or educational status ( p>0,05). Particularly health care team's attention, trust and courtesy came forward as strong points. The weaknesses noted as difficulties in booking an outpatient doctor visit appointment because the phone line was busy or the secretary was not courteous, the excessive amount of time and effort it required to get laboratory and radiology results. Conclusion: The health care system is basically a service based industry and customer satisfaction is at utmost importance just as in other service-oriented sectors. We hope this study will shed light in that area and Turkish health care providers will pay closer attention to how their patients feel about the services that they are getting.
Keywords: chemotherapy; cancer care units; Turkey; patient centered care; patient satisfaction; CARE